DIGITAL BRANDING STRATEGY FOR HALAL FASHION PRODUCTS IN INCREASING MARKETING - Elensya Eka Shintya Putri; Amin Awal Amarudin; Ashlihah Ashlihah; Nurul Suhada Ismail; Ahmad Munir Hamid (Universitas Islam Darul 'ulum Lamongan, 2025)
Brands become things that can make an impression and keep consumers to be loyal customers. Building the right personal branding is the key to winning competition in the era of digitalization by doing digital branding. The aim of this research is to understand and describe the digital branding strategy that halal fashion products can enhance marketing. This research uses qualitative methods. It was carried out at Agen Rabbani Kota Jombang which is located at Jl. Kusuma Bangsa No. 73, Pulo Lor, Kec.Jombang, Kab. Jomban with primary and secondary data collection. Then a descriptive analysis of the data is carried out to draw conclusions. Based on the studies already carried out, the conclusion can be drawn that the digital branding strategy (X1) has a significant positive impact on marketing improvement. The results of research on halal fashion product variables (X2) have an impact on the implementation of digital Branding strategy in enhancing marketing at Agen Rabbani Kota Jombang.